STUDENT VOLUNTEERISM IN THE REHABILITATION OF A CHILD WITH FRACTURA OLECRANI: PRESENTATION OF CLINICAL CASE - Gergana Nenova; Mina Ivelinova (Peytchinski Publishing, 2022)
Aim: To monitor the rehabilitation progress of a child with fracturaolecrani with the participation of a student volunteer in the multidisciplinary team. Methods: K.J. is an 11-year-old child admitted for rehabilitation in the Clinic of Orthopaedics and Traumatology at University Hospital "St. Marina"- Varna. In 2011 K.J. suffered a fracture in the area of the right elbow joint and underwent surgery with the placement of three Kirschner needles. Four years later, the patient suffered the same fracture and underwent surgery with the placement of two Kirschner needles. Oedema, joint deformation, severely limited range of motion, contractures, muscle hypotrophy and psychotrauma, were found after examination by an orthopaedist and a kinesitherapist. The individual kinesitherapeutic approach is focused on reducing oedema; improving activity; preventing complications; stimulating the patient's participation in social activities. Results: With the help of functional examinations (centimetre measurements, anglemetry and MMT), we established significant restoration of the upper extremity's function and reduction of the oedema. The minimal differences result from the rough operative cicatrix and slight joint deformation. The range of motion is restored to a large extent, as the deficit of 5-10 degrees is not essential in daily activities and could be further restored. Conclusions: the application of an individual approach in the multidisciplinary team's work, with the participation of a student volunteer, helps build a trustworthy relationship with the child patient. The inclusion of a student volunteer in the multidisciplinary team improves communication with vulnerable population groups and contributes to a faster physical and mental recovery.